2018
DOI: 10.1155/2018/5970852
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Coexpression of Epithelial Cell Adhesion Molecule and Alpha-Fetoprotein in Hepatocellular Carcinoma

Abstract: Background and Aim The epithelial cell adhesion molecule (EpCAM) has been proposed as a marker for cancer stem cells in human hepatocellular carcinoma (HCC) as well as in the development of novel target therapies. This study aimed to investigate the immunohistochemical expression of EpCAM and alpha-fetoprotein (AFP) in HCC patients and their association with clinicopathological characteristics. Methods This study included Child-Pugh A HCC patients undergoing curative surgical resection. Results A significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…Former studies reported significant association of EpCAM expression in HCC with high tumor grade and AFP level (36,37). In our current study, the expression levels of AFP and EpCAM were significantly higher in the HCC group relative to the HCV and control groups.…”
Section: Discussionsupporting
confidence: 56%
“…Former studies reported significant association of EpCAM expression in HCC with high tumor grade and AFP level (36,37). In our current study, the expression levels of AFP and EpCAM were significantly higher in the HCC group relative to the HCV and control groups.…”
Section: Discussionsupporting
confidence: 56%
“…Epithelial cell adhesion molecule (EpCAM) is a type I transmembrane glycoprotein, acting as a Ca 2+ -independent homophilic cell adhesion molecule [13]. EpCAM has been reported to be involved in malignant proliferation, invasion, metastasis, and tumor recurrence [1].…”
Section: Discussionmentioning
confidence: 99%
“…EpCAM expression was identified as brownish fine granular cytoplasmic and/ or membranous staining. EpCAM-positive expression was considered when >10% of cells demonstrated a moderate or strong stain 18 …”
Section: Methodsmentioning
confidence: 99%
“…Ep-CAM-positive expression was considered when > 10% of cells demonstrated a moderate or strong stain. 18 A semi-quantitative immunoreactivity scoring system (IRS) was based on the proportion of positive cells and intensity of staining to determine the expression status as follow; 0 (negative, <5%); 1+ (weak, 5% to 30%); 2+ (moderate, 30% to 60%); and 3+ (strong, > 60%). 19 Ki67-positive expression was identified as brownish nuclear staining.…”
Section: Immunohistochemistry Interpretationmentioning
confidence: 99%